(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
According to the data presented here, the historic non-Indo-European languages of Spain, Iberian and Aquitanian —ie., old Basque— would not be pre-Indo-European relicts, as traditionally assumed, but the results of intrusive newcomers that entered the Iberian Peninsula in relatively recent times.